A review of remote sensing utilization for identifying and monitoring change of land cover within coastal ecosystems of the Caribbean - Gilbert, Marena Ann (URJ-UCCS: Undergraduate Research Journal at UCCS, 2015)
The dynamic ecosystems of the Caribbean are part of one of the most critical hotspots on Earth (Meyers et al., 2000). The role of remote sensing in our technologically advanced world, places inhabitants of the Caribbean in an advantageous position to utilize this amazing resource in order to enhance and monitor their environment. Mangrove forests, coastal sand body areas and coastal water environments can be better understood and managed through satellite, aerial and ground level remote sensing. This review identifies specific aspects of remote sensing that are being used to their full advantage for conducting land cover change monitoring and analysis in the Caribbean and those capabilities that are underutilized.